Impact Of Vitamin - A Supplementation On Diarrhoea among Children 12 - 71 Months Of Age In Baroda Cantonment A Double Blind Randomised Cntrolled Trail - Kotecha Prakash V; Bhargava S (Wolters Kluwer Medknow Publications, 1998)
Research question: Does vitamin- A supplementation in children under five of age reduce diarrhoea incidence and its duration? Objectives: To study whether vitamin â€" A supplementation among children of 12-71 months of age reduces the risk and rate of diarrhoea and qualify if it does. Study design: Randomised double â€" blind controlled trail. Settings: Military Hospitals, Baroda Participants: Children of 12- 71 months of age of military staff members of Baroda cantonment Results and conclusions: The study suggested a reduction of risk and rate of diarrhoea in vitamin A supplemented group as compared to the placeup by about 23% and 22% respectively. However, it failed to show any reduction in the duration of an episode.